Performance Enhancement of a-C:Cr Thin Films Deposited on 316L Stainless Steel as Bipolar Plates via a Thin Ti Layer by Mid-Frequency Magnetron Sputtering for PEMFC Application - Yuxing Zhao; Song Li; Saiqiang Wang; Ming Ma; Ming Chen; Jiao Yang; Chunlei Yang; Weimin Li (Energies)
Ti/a-C:Cr multilayer films were deposited on 316L stainless steel (SS316L) substrates using medium-frequency alternating current magnetron sputtering, with a single-layer a-C:Cr film also prepared on a titanium substrate. The influence of sputtering pressure on the film’s structure and properties was systematically investigated. Film morphology and microstructure were analyzed via X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and atomic force microscopy (AFM). At a pressure of 1.4 MPa, the interfacial contact resistance (ICR) of SS316L bipolar plates (BPPs) coated with the films reached as low as 3.30 mΩ·cm2, while that of titanium BPPs was 2.90 mΩ·cm2. Under simulated proton exchange membrane fuel cell (PEMFC) cathode conditions (70 °C, 0.6 V vs. SCE, 0.5 M H2SO4, 5 ppm HF solution), the corrosion current density, Icorr, reached optimal values of 0.69 μA·cm−2 for SS316L and 0.62 μA·cm−2 for titanium. These results demonstrate that parameter optimization enables SS316L BPPs to functionally replace titanium counterparts, offering significant cost reductions for metal BPPs and accelerating the commercialization of PEMFC technology.